Effects of Artificial Flooding for Hydroelectric Development on the Population of Mansonia humeralis (Diptera: Culicidae) in the Paraná River, São Paulo, Brazil - Marcia Bicudo de Paula; Almério de Castro Gomes; Delsio Natal; Ana Maria Ribeiro de Castro Duarte; Luís Filipe Mucci (Journal of Tropical Medicine)
The closure of two phases of the dam at the Porto Primavera Hydroelectric Plant on the Paraná River flooded a flawed system located in the Municipality of Presidente Epitácio, São Paulo state, favoring the proliferation of aquatic weeds. This study aimed to observe the population of Mansonia humeralis in the area, monitoring the richness, diversity, and dominance of this species both before and during different phases of reservoir flooding as well as evaluate its possible consequences concerning human and animal contact. Adult mosquitoes were collected monthly in the following periods: at the original level, after the first flood, and after the maximum level had been reached between 1997 and 2002. Collection methods used were an aspirator, a Shannon trap, and the Human Attractive Technique. A total of 30,723 mosquitoes were collected, Ma. humeralis accounting for 3.1% in the preflood phase, 59.6% in the intermediate, and 53.8% at maximum level. This species is relevant to public health, since the prospect of continued contact between Ma. humeralis and the human population enhances the dam’s importance in the production of nuisance mosquitoes, possibly facilitating the transmission of arboviruses. Local authorities should continue to monitor culicid activity through sustainable entomological surveillance.